Information Technologies Of The XXI Century Teacher Education: The Role Of Pedagogical Software In Developing Digital Literacy Skills - Khalikova Gulnora Tokhtamurodovna (Global Scientific Publishing, 2024)
Equipping students with digital literacy skills is essential to success in today's world. This article examines the role of pedagogical software in developing these skills in the context of computer science and information technology teacher education. It explores the landscape of digital literacy skills, analyzes the benefits and limitations of pedagogical software, and discusses how its integration can improve computer science and information technology teacher education programs.
Keywords: Pedagogical software; teacher training; informatics and information; technology integration